Emblems and the natural world - Enenkel, Karl A. E.; Smith, Paul J. (Intersections, 2017)
Since its invention by Andrea Alciato, the emblem is inextricably connected to the natural world. Alciato and his followers drew their inspiration heavily from it. For their information about nature, the emblem authors were greatly indebted to ancient natural history, the medieval bestiaries, and the 15th- and 16th-century proto-emblematics, especially the imprese. The natural world became the main topic of, for instance, Camerarius?s botanical and zoological emblem books, and also of the ?applied? emblematics in drawings and the decorative arts. This interdisciplinary volume aims to address the multiple connections between emblematics and Natural History in the broader perspective of their underlying artistic, political and religious ideologies
"conference 'Emblems and the Natural World (1500-1700), which took place at the Westfälische Wilhelms-Universität Münster in December 2015" (Seite IX)
Keywords: Geschichte 1500-1700; Konferenzschrift -- Westfälische Wilhelms-Universität Münster -- 2015 -- Münster (Westf); Aufsatzsammlung; Konferenzschrift -- 2015 -- Münster (Westfalen); Pflanzendarstellung; Tierdarstellung; Naturdarstellung; Emblem; Naturwissenschaften; Zoologie; Emblemliteratur; Fabeltiere